1996
DOI: 10.1161/01.res.78.6.954
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Mitogen-Activated Protein Kinase Using an Antisense Oligodeoxynucleotide Approach Downregulates the Phenylephrine-Induced Hypertrophic Response in Rat Cardiac Myocytes

Abstract: An antisense oligodeoxynucleotide (ODN) approach was used to investigate whether mitogen-activated protein kinase (MAPK) is necessary for the hypertrophic response in cardiac myocytes. A phosphorothioate-protected 17-mer directed against the initiation of translation sites of the p42 and p44 MAPK isoform mRNAs was introduced into cultured cardiac myocytes by liposomal transfection. At an antisense ODN concentration of 0.2 mumol/L, p42 MAPK protein was reduced by 82% (immunoblot) after 48 hours, and p42 and p44… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
118
1
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(126 citation statements)
references
References 30 publications
3
118
1
1
Order By: Relevance
“…In this study, the functional activity of the various pharmacological antagonists closely paralleled their ability to inhibit MAPK activity in these cultures. By inference, this suggests that MAPK participates in the signaling cascade linking mechanical strain to acquisition of the hypertrophic phenotype, a hypothesis that draws support from the studies of others (31)(32)(33). The activity of the inhibitors did not correlate well with their ability to inhibit JNK/SAPK activity.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…In this study, the functional activity of the various pharmacological antagonists closely paralleled their ability to inhibit MAPK activity in these cultures. By inference, this suggests that MAPK participates in the signaling cascade linking mechanical strain to acquisition of the hypertrophic phenotype, a hypothesis that draws support from the studies of others (31)(32)(33). The activity of the inhibitors did not correlate well with their ability to inhibit JNK/SAPK activity.…”
Section: Discussionmentioning
confidence: 74%
“…MAPK, for example, is known to be activated by both the biochemical agonists of hypertrophy as well as mechanical strain (23, 27, 30 -32), and dominant-negative mutants of MAPK and MAPK kinase (MEK), which lies immediately upstream from MAPK in the effector cascade (34), suppress phenylephrine induction of a transiently transfected rat ANP promoter (31). Moreover, antisense oligonucleotides directed against MAPK have been shown to reduce phenylephrine-dependent increments in ANP mRNA levels and ANP promoter activity while, at the same time, suppressing sarcomerogenesis and increments in cell size that typically accompany hypertrophy induced by this agent (33). However, Post et al (32) recently reported that activation of MAPK does not routinely parallel the development of hypertrophy in the cultured myocyte model, and in their hands, dominant-negative mutants of the MAPK pathway failed to suppress phenylephrine-mediated activation of a transfected ANP promoter.…”
mentioning
confidence: 99%
“…1B and quantification of cell size in Fig. S1E) (16,17). Strikingly, ERK2 T188A did not enhance H 2 O 2 -induced apoptotic cell death, as determined by terminal deoxynucleotidyl transferase dUTP nick-end labeling (TUNEL) (Fig.…”
Section: Resultsmentioning
confidence: 92%
“…Indeed, the activation of MAPK by various trophic factors appears important in the intracellular-signaling pathways leading to hypertrophy (17)(18)(19). For instance, blocking ERK protein synthesis using antisense oligodeoxynucleotides reduces transcriptional and morphological responses to PE in rat cardiomyocytes (30). NPY has been shown to potentiate the effects of various vasoactive substances including ␣-receptor agonists (6,8).…”
Section: Discussionmentioning
confidence: 99%